2002 (3WQjbI dEXgGQ MHc dCWaGdc (B/s - (3gGjfR, SjfOjs ((3HjQhJ (B:s (3ecJHI LQjQ,s, 2006)
(3jgJe gPG GdcJGH HYde faS GdCWaGd agh jbOe eLehYI TjbI ef GdWQb GdeHgLI dJXgQ dWadc eOi GgJeGec Hg(B.s
Keywords: (3GdCWaGds -- (3Yde faSs